Problem-Based Learning with a Deep Learning Orientation in Elementary Science and Social Studies: Fostering Conceptual Understanding and Student Engagement in Grade IV - Rini Ramadan; Rizal Rizal; Pahriadi Pahriadi; Nashrullah Nashrullah; Muhammad Nazimuddin AL Kamil; Surahman Wilade (Papanda Publisher, 2026)
Conventional, teacher-centered instruction in Indonesian elementary classrooms frequently results in surface-level understanding and limited student engagement, particularly in Integrated Science and Social Studies (IPAS). Addressing this gap, this study examined the implementation of a Problem-Based Learning (PBL) model oriented toward a Deep Learning approach—encompassing mindful, meaningful, and joyful learning—in Grade IV IPAS instruction. A Classroom Action Research design was employed across two cycles involving 20 fourth-grade students at SDN Lahuafu, Morowali Regency, during the 2025/2026 academic year. Data were collected through structured classroom observations, semi-structured interviews, a 23-item Likert-scale questionnaire (α = 0.87), and learning outcome tests, and analyzed using Miles and Huberman's interactive model alongside descriptive statistics. Findings indicate that students progressed from passive reception to active contextual reasoning, demonstrating the capacity to analyze and justify conceptual distinctions in real-life contexts. The student response questionnaire yielded an aggregate score of 91% (